2005
DOI: 10.4028/www.scientific.net/msf.495-497.1535
|View full text |Cite
|
Sign up to set email alerts
|

Texture-Based Explicit Finite-Element Analysis of Sheet Metal Forming

Abstract: An explicit integration algorithm using a texture-based plastic potential and isotropic hardening has been developed and implemented into a commercial explicit finite-element software program through a user material subroutine (VUMAT in ABAQUS/Explicit). Simulations of cup drawing of an IF-steel are presented and compared to both experimental data and calculation results obtained with a previously developed fully implicit approach (UMAT in ABAQUS/Standard). The explicit formulation has the advantage of being m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Experience with the Quantic method has shown that n in G n as given by Eq. (4)-(6) should be at least 4, preferably 6 (Van Bael et al, 2003;Ristic et al, 2005). G n as given by Eq.…”
Section: Identification Of the Parametersmentioning
confidence: 99%
“…Experience with the Quantic method has shown that n in G n as given by Eq. (4)-(6) should be at least 4, preferably 6 (Van Bael et al, 2003;Ristic et al, 2005). G n as given by Eq.…”
Section: Identification Of the Parametersmentioning
confidence: 99%
“…A mathematical criterion could be formulated to ensure the overall convexity of the yield surface, and an iterative algorithm was proposed to slightly modify the fitted parameters in order to satisfy that criterion. The Quantic method has been implemented in both implicit and explicit finite-element software programs through user material routines [9]. In spite of the guaranteed convexity and the resulting reliability of the method, the Quantic method has the drawback of being formulated in strain rate space but not in stress space.…”
Section: Introductionmentioning
confidence: 99%